Electromagnetic nondestructive evaluation (XVIII) - Chen, Zhenmao; Xie, Shejuan; Li, Yong (Studies in applied electromagnetics and mechanics, 2015)
The workshop focused on research into the theory and application of ENDE methods, and provided a forum for the exchange of ideas and discussion of recent developments.